PENERAPAN MANAJEMEN SARANA PRASARANA SEBAGAI UPAYA MENCAPAI STANDAR SARANA PRASARANA PENDIDIKAN DI SMA KANJENG SEPUH (SMAKS) SEDAYU GRESIK - Hakim, Khoirul; Suyanto, Suyanto; Wahyudi, M.Furqon (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe and analyze the implementation of educational facilities and infrastructure management in achieving educational facilities and infrastructure standards at Kanjeng Sepuh Senior High School, Sedayu Gresik. A qualitative case study approach was employed. Data collection techniques included in-depth interviews, observation, and documentation involving school leadership, facilities and infrastructure managers, and teachers. Qualitative data analysis was conducted through data reduction, data presentation, and conclusion drawing with triangulation to ensure trustworthiness. The results show that management functions covering planning, procurement, maintenance, and evaluation have been implemented systematically and participatively. The achievement of educational facilities and infrastructure standards is classified as good in terms of the availability of core learning facilities, maintenance of the learning environment, and classroom capacity ratios, but remains suboptimal in the provision of inclusive facilities and the development of digital learning infrastructure. Supporting factors include strong managerial leadership, internal and external collaboration, and the utilization of endowment-based funding as an alternative financial source, while limited budgets remain the primary constraint.